Analisis Respon Vietnam dalam Menghadapi Kebijakan Illegal Fishing Indonesia di Zona Ekonomi Eksklusif Perairan Natuna - Tia Maulida; Indra Kusumawardhana (Insignia: Journal of International Relations, 2020)
This design/research on Vietnam's response to the IUU Fishing Indonesia "Sink the Vessels" policy which has sunk 272 Vietnamese vessels from 2014-2018, with the aim of providing an understanding of Vietnam's strategy in maintaining its relationship with Indonesia and the reasons why Vietnam responded to the policy it is not aggressive. This study uses defensive realism approach through four assumptions from Jeffrey W. Taliaferro. The method used is a qualitative research model that is descriptive in nature with literature study data collection techniques through the collection of data and information and reliable sources. The results show that based on the four basic assumptions of Taliaferro realism, namely Vietnam experiences a security dilemma that is not focused on Indonesia, the existence of complex water conflicts in the region, Vietnam's military capabilities under Indonesia and Vietnam's domestic politics which have a tendency to maintain good relations with Indonesia.